The relationship between immature platelet fraction and severity of acute bronchiolitis - Doğan, Murat; Köse, Mehmet; Öztürk, Mehmet Adnan; Hangül, Melih; Aslaner, Hümeyra (The Turkish Journal of Pediatrics, 2021)
Background and Objectives. Acute bronchiolitis is one of the most common reasons for hospitalization in infants. Although patients with acute bronchiolitis generally have a good prognosis, death can also occur. In this study, we evaluate the immature platelet fraction (IPF) as an indicator of the severity of acute bronchiolitis. Methods. In our study, 179 patients diagnosed with acute bronchiolitis were divided into three groups as mild (n: 48; 26.8%), moderate (n: 104; 58.10%) and severe (n: 27; 15.1%) bronchiolitis. There were 80 healthy children in the control group. The diagnostic capacity of IPF and hematological parameters (platelet distribution width (PDW), mean platelet volume (MPV), white blood cell count (WBC), and platelet count (PLT)) values to predict severity of acute bronchiolitis was evaluated using receiver operating characteristic (ROC) curves and their respective areas under the curves (AUCs) calculated with 95% confidence intervals. Results. The IPF value of patients with acute bronchiolitis was significantly higher than the healthy group (p < 0.001). In addition, a positive correlation was observed between clinical severity of bronchiolitis and IPF. The ROC curve analysis indicated that the IPF cut-off point for predicting severity of acute bronchiolitis was > 3.2% (Sensitivity of 84%, specificity of 97%). We found that the AUCs for IPF, MPV, PDW, WBC and PLT were statistically significant for bronchiolitis relative to the healthy control group. The parameter with the greatest AUC value was IPF. Conclusion. The IPF may present for diagnosing and evaluating the clinical severity of acute bronchiolitis in children.
Keywords: acute bronchiolitis; children; immature platelet fraction